1994
DOI: 10.1111/j.1464-410x.1994.tb07114.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the evaluation of asymptomatic microscopic haematuria in young men

Abstract: Even in young patients, microscopic haematuria should be investigated and followed thoroughly. Renal biopsy seems to be optional: once a diagnosis is established repeated and unnecessary examinations can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…However, Shu et al highlighted the importance of performing a renal biopsy on IMH patients because minimal urinary abnormality with normal renal function at presentation does not necessarily imply a favorable outcome in certain patients; in addition, tubular atrophy and interstitial fibrosis, but not glomerular change, correlate with a worse prognosis [23]. Sparwasser et al [24] suggested that a kidney biopsy be considered optional, and that once a diagnosis is established, repeated and unnecessary examinations can be avoided in young patients with persistent hematuria. Shen et al [4] suggested that the urinary albumin/creatinine ratio, serum IgA level, and serum IgA/C3 ratio can serve as non-invasive markers to predict the necessity of a renal biopsy in adult patients with IMH.…”
Section: Discussionmentioning
confidence: 99%
“…However, Shu et al highlighted the importance of performing a renal biopsy on IMH patients because minimal urinary abnormality with normal renal function at presentation does not necessarily imply a favorable outcome in certain patients; in addition, tubular atrophy and interstitial fibrosis, but not glomerular change, correlate with a worse prognosis [23]. Sparwasser et al [24] suggested that a kidney biopsy be considered optional, and that once a diagnosis is established, repeated and unnecessary examinations can be avoided in young patients with persistent hematuria. Shen et al [4] suggested that the urinary albumin/creatinine ratio, serum IgA level, and serum IgA/C3 ratio can serve as non-invasive markers to predict the necessity of a renal biopsy in adult patients with IMH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tubular atrophy and interstitial fibrosis, but not glomerular change, correlated with a worse prognosis. Sparwasser et al [14] suggested that a kidney biopsy is considered optional; once a diagnosis was established, repeated and unnecessary examinations can be avoided in young patients with persistent hematuria. We aimed to demonstrate the importance of renal biopsy and essentiality of therapy to patients with IgAN and isolated hematuria by analyzing the pathological features of them.…”
Section: Discussionmentioning
confidence: 99%
“…IgA nephropathy, a form of glomerulonephritis defined histologically by glomerular IgA deposits, accounted for the majority of cases with a glomerular source. 7 In a series of 165 patients, renal biopsies were performed after renal imaging and cystoscopy. No abnormalities were noted on renal biopsy in 87 patients.…”
Section: Clinical Relevancementioning
confidence: 99%